A cross-sectional examination of service complexity in youths with co-occurring autism spectrum disorder and psychiatric or medical diagnoses across service sectors - Semovski, Valbona; King, Colin; Lapshina, Natalia; Stewart, Shannon L. (Frontiers in Psychology, 2023)
Autism spectrum disorder is a heterogeneous, life-long and complex condition. Youth diagnosed with autism spectrum disorder require several supports addressing core symptoms associated with the disorder, but also those resulting from co-occurring mental and physical health conditions. As a result, their care is overseen by numerous professionals spanning a multitude of service sectors, but communication between sectors is hindered due to the absence of a standardized assessment system to identify and triage youth to services. A paucity of information surrounding this population’s service use lingers and a siloed delivery system persists. Using archival data collected from 1020 youth between 12 and 18 years of age, this study explored service complexity among autistic youth with and without psychiatric and medical co-occurrences in Ontario, Canada. In doing so, a negative binomial regression was utilized to investigate which predisposing, enabling and need variables were associated with service complexity. Results revealed that experiencing financial difficulties was not associated with service complexity. However, age, sex, caregiver distress, comorbidity, intellectual disability and evaluated health status were significant predictors. Female youth with distressed caregivers, diagnosed with two or more conditions in addition to autism spectrum disorder and who required longer durations of programming had greater mental health service complexity scores. Yet, youth with an intellectual disability had lower service complexity scores. Clinical implications of this study are discussed to inform future investments into mental health efforts for autistic youth.